Morphology and dynamics of sporadic E layers observed by amateur radio - WenYu Hao; Tao Yu; Yang-Yi Sun; Jin Wang; LiHui Qiu (Earth and Planetary Physics, 2025)
The Es layer is a thin layer that concentrates metallic ions in the mesosphere and lower thermosphere (MLT) region. When it occurs, it can affect the performance of the Global Navigation Satellite System and high/very high frequency (HF/VHF) radio communications. Previous studies mainly focused on the one-dimensional structure of Es layer in the vertical direction. However, due to the limitation of observations, the horizontal structure of Es layers is not yet fully understood. This study investigated the horizontal structure of Es layers using amateur radio data in the European sector during the summer of 2020. Statistical analysis shows that the horizontal structure of Es layer is mainly elongated in the east−west direction. In addition, we investigated the dynamics of the Es layers, which primarily propagates in the northeast−southwest direction with a speed of 50−200 m/s. The results provide us a way for obtaining the horizontal structure and dynamic features of Es layers, which can help improve our understanding of the formation and evolution of Es layers.